Impact of Earthing System Designs and Soil Characteristics on Tower Footing Impedance and Ground Potential Rise: A Modelling Approach for Sustainable Power Operation - Nur Alia Farina Mohamad Nasir; Mohd Zainal Abidin Ab Kadir; Miszaina Osman; Muhamad Safwan Abd Rahman; Ungku Anisa Ungku Amirulddin; Mohd Solehin Mohd Nasir; Nik Hakimi Nik Ali; Nur Hazirah Zaini (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Indexed by WOS/Scopus/ERA